2019
DOI: 10.1093/molbev/msz197
|View full text |Cite
|
Sign up to set email alerts
|

HyPhy 2.5—A Customizable Platform for Evolutionary Hypothesis Testing Using Phylogenies

Abstract: HYpothesis testing using PHYlogenies (HyPhy) is a scriptable, open-source package for fitting a broad range of evolutionary models to multiple sequence alignments, and for conducting subsequent parameter estimation and hypothesis testing, primarily in the maximum likelihood statistical framework. It has become a popular choice for characterizing various aspects of the evolutionary process: natural selection, evolutionary rates, recombination, and coevolution. The 2.5 release (available from www.hyphy.org) incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
333
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(336 citation statements)
references
References 23 publications
3
333
0
Order By: Relevance
“…Thus, attaining additional population data and whole genomes of multiple Tribolium species will be valuable for allowing further tests of putative positive selection on the X chromosome using complementary approaches to the ones employed here. These methods could include, for example, McDonald-Kreitman tests (Mcdonald and Kreitman 1991;Meisel and Connallon 2013;Rousselle et al 2016;Murga-Moreno et al 2019;Pinharanda et al 2019) and branch-site analyses of dN/dS in multiple species (Yang 2007;Kosakovsky Pond et al 2019). Population data analyses will also allow measures of recombination rates (Stumpf and Mcvean 2003;Comeron et al 2012), which has been suggested to influence the faster-X effect ) and assessments of potential roles of effective population size (Mank et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, attaining additional population data and whole genomes of multiple Tribolium species will be valuable for allowing further tests of putative positive selection on the X chromosome using complementary approaches to the ones employed here. These methods could include, for example, McDonald-Kreitman tests (Mcdonald and Kreitman 1991;Meisel and Connallon 2013;Rousselle et al 2016;Murga-Moreno et al 2019;Pinharanda et al 2019) and branch-site analyses of dN/dS in multiple species (Yang 2007;Kosakovsky Pond et al 2019). Population data analyses will also allow measures of recombination rates (Stumpf and Mcvean 2003;Comeron et al 2012), which has been suggested to influence the faster-X effect ) and assessments of potential roles of effective population size (Mank et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to determine whether bats, and specifically the family Rhinolophidae, are under strong selection to adapt to viruses we used the adaptive branch-site random effects model test of positive selection, aBSREL 21 , as implemented in HyPhy, version 2.5.8 41 , using a pruned subset of five phylogenetic hypotheses chosen from the pseudo-posterior distribution of Upham et al 17 to account for phylogenetic uncertainty. We tested three conditions: 1) in which the branch leading to Rhinolophidae was considered the foreground branch; 2) in which the branch leading to the common ancestor of all bats was considered the foreground branch; and 3) in which all branches were tested without a priori specification of background and foreground branches.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…1.6.10; with option -bb 10000 -alrt 1000). The evidence for selection across gene families was tested using the HyPhy 112,113 platform in the webserver of datamonkey 114116 . According to the recombination breakpoints analysed by the Genetic Algorithm for Recombination Detection 117 (GARD), the alignment was trimmed for analysing selection using Single-Likelihood Ancestor Counting 118 (SLAC) and Mixed Effects Model of Evolution 119 (MEME) with P <0.1.…”
Section: Methodsmentioning
confidence: 99%